Comparing the value of bioproducts from different stages of anaerobic membrane bioreactors. (August 2016) - Khan, M.A.; Ngo, H.H.; Guo, W.S.; Liu, Y.W.; Zhou, J.L.; Zhang, J.; Liang, S.; Ni, B.J.; Zhang, X.B.; Wang, J.
Graphical abstract: Highlights: Current AnMBRs mainly focuses on final bioproducts – methane. Technical feasibility shows the comparable value of intermediate AnMBR bioproducts. Alternate AnMBRs based VFA and biohydrogen production is considerable. VFA and biohydrogen production are a cost recovery option for AnMBR. Environmental impacts are associated with different AnMBR bioproducts. Abstract: The anaerobic digestion process in anaerobic membrane bioreactors is an effective way for waste management, energy sustainability and pollution control in the environment. This digestion process basically involves the production of volatile fatty acids and biohydrogen as intermediate products and methane as a final product. This paper compares the value of bioproducts from different stages of anaerobic membrane bioreactors through a thorough assessment. The value was assessed in terms of technical feasibility, economic assessment, environmental impact and impact on society. Even though the current research objective is more inclined to optimize the production of methane, the intermediate products could also be considered as economically attractive and environment friendly options. Hence, this is the first review study to correlate the idea into an anaerobic membrane bioreactor which is expected to guide future research pathways regarding anaerobic process and its bioproducts.